The ravages of conflict and the echoes of poverty: Community empowerment and recovery a decade after the Wukari crises in Taraba State, Nigeria - Ja'afaru, Sharifatu Gago (IAIN Madura, 2025)
This study examines the historical, socio-economic, and psychological impacts of the violent conflicts that affected the Wukari communities within Taraba State. It explores the socio-economic effects of prolonged instability, social dislocation, and impoverishment, as well as the psychosocial trauma inflicted on communities. Additionally, it examines the strategies employed by socio-economically traumatized persons and communities to recover, rebuild, and transform their conflicts, thereby reclaiming their agency. The study aimed to investigate the socio-economic effects of crises, the media's influence on the recuperation phenomenon, remedial community engagement, and the contribution of community empowerment approaches to poverty alleviation and the intertwined processes of sustainable peace and social development. The researcher employed a qualitative method, utilizing in-depth interviews with forty respondents, comprising teachers, farmers, displaced persons, women, and youth who have all survived socio-occupational crises. The poverty, devastation of agricultural land, and destruction of social capital that resulted from the crises fostered social disintegration, mistrust, and resource-embedded displacement. While the national media provided only occasional coverage, local digital media played a crucial role in advancing self-help initiatives during the socio-occupational crises, as well as facilitating local social cooperation. Community resilience was demonstrated through grassroots women's cooperatives, faith-based relief efforts, and small-scale empowerment initiatives; however, the lack of state support remained a significant obstacle. This study, informed by the Social Capital Theory, posits that the restoration of the trust, networks, and cooperation dimensions of social capital is essential for sustainable recovery and must accompany the restoration of livelihoods in the Wukari Local Government Area (LGA), Taraba State. Wukari recovery, as a key conclusion of this study, should be less focused on physical reconstruction and more on bridging the recovery of empowerment and social cohesion. Therefore, this study argues that Wukari (LGA) post-conflict, the strategic recovery empowerment and resilience mechanisms, should be centered on the recovery consolidation of trust-building, empowerment, active media and social media advocacy, the implementation of the peace committee reports, operationalised with strategic public-private partnerships for the reconstruction of sustainable infrastructure, and inform the post-conflict reconstruction.[Studi ini meneliti dampak historis, sosial ekonomi, dan psikologis dari konflik kekerasan yang melanda komunitas Wukari di Negara Bagian Taraba. Penelitian ini mengeksplorasi dampak sosial ekonomi dari ketidakstabilan yang berkepanjangan, ketercerabutan sosial, dan kemiskinan; trauma psikososial yang diderita masyarakat; serta strategi yang digunakan individu dan komunitas yang mengalami trauma sosial ekonomi untuk pulih, membangun kembali, dan mentransformasikan konflik mereka guna merebut kembali kendali atas kehidupan mereka. Tujuan penelitian ini adalah untuk menyelidiki dampak sosial ekonomi dari krisis, pengaruh media terhadap proses pemulihan, bentuk keterlibatan komunitas yang bersifat pemulihan, serta kontribusi pendekatan pemberdayaan masyarakat terhadap pengentasan kemiskinan dan keterkaitan antara perdamaian berkelanjutan serta pembangunan sosial. Peneliti menggunakan metode kualitatif dengan wawancara mendalam terhadap empat puluh responden, yang terdiri atas guru, petani, pengungsi, perempuan, dan pemuda yang semuanya merupakan penyintas krisis sosial-occupational. Kemiskinan, kerusakan lahan pertanian, dan hancurnya modal sosial akibat krisis tersebut menimbulkan disintegrasi sosial, ketidakpercayaan, dan perpindahan penduduk yang berakar pada sumber daya. Sementara media nasional hanya memberikan liputan sesekali, media digital lokal memainkan peran penting dalam mendorong inisiatif swadaya selama krisis sosial-ekonomi serta memfasilitasi kerja sama sosial di tingkat lokal. Ketahanan masyarakat ditunjukkan melalui koperasi perempuan akar rumput, upaya bantuan berbasis keagamaan, dan inisiatif pemberdayaan berskala kecil; namun, kurangnya dukungan pemerintah tetap menjadi hambatan besar. Studi ini, yang berlandaskan pada Teori Modal Sosial, berpendapat bahwa pemulihan dimensi kepercayaan, jaringan, dan kerja sama dalam modal sosial merupakan hal yang penting bagi pemulihan berkelanjutan dan harus berjalan seiring dengan pemulihan mata pencaharian di Wilayah Pemerintahan Lokal (LGA) Wukari, Negara Bagian Taraba. Kesimpulan utama dari penelitian ini adalah bahwa pemulihan Wukari seharusnya tidak semata-mata berfokus pada rekonstruksi fisik, melainkan lebih diarahkan pada pemulihan pemberdayaan dan kohesi sosial. Oleh karena itu, penelitian ini menegaskan bahwa pasca-konflik di Wukari (LGA), mekanisme pemberdayaan dan ketahanan strategis untuk pemulihan harus berpusat pada konsolidasi kepercayaan, pemberdayaan, advokasi melalui media dan media sosial, pelaksanaan laporan komite perdamaian, serta dioperasionalkan melalui kemitraan strategis antara sektor publik dan swasta untuk rekonstruksi infrastruktur berkelanjutan dan perencanaan pembangunan pascakonflik].